Alfalfa for the Kansas farmer - Birch, Wallace Newton (My University, 1904)
Introduction: When we see the vast amount of wheat end corn which is annually shipped out of our state we are forced to exclaim, "How long can this continue?" For the last ten years Kansas has produced an average annual crop of 149,127,402 bushels of corn and 47,451,487 bushels of wheat. Of this immense product only a comparatively small portion is fed or consumed within the borders of the state. The large part is shipped each year into other states and to foreign countries. What does this mean? It means that if we do not stop farming on the robbery plan we will soon be where the farmers of Eastern United State are who have either abandoned their farms or are compelled to spend vast sums for fertilizers each year in order to secure paying crops. The little state of Maryland alone spends over six millions of dollars annually for commercial fertilizers. Kansas farmers have not been concerned about, maintaining the fertility of the land. They crop the land continuously, selling the grain and burning the straw, stubble and stalks in order to get them out of the way. This is simply robbing the soil of its fertility and the time is sure to come when the Kansas farmer will realize that such robbery never pays in the long run.
The place alfalfa should take in Kansas farming
Citation: Birch, Wallace Newton. Alfalfa for the Kansas farmer. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Kansas; Kansas Agriculture; Agriculture; Problems in Farming Logistics; Theses